La bonne distance. Réflexions sur le phénomène P. E. Trudeau - Schwimmer, Éric (Anthropologica, 2022)
The Levi-Straussian theory of the right distance is applied here to the relations between Quebec and the Rest of Canada, on the basis of two mythic constructions: those of P. E. Trudeau and J. Ferron. According to that type of theory, in any society, the level of relations of communal proximity tends to preserve the right distance from the higher level of empires and supra-national confederations. Analysis of the negotiations concerning the repatriation of the Canadian constitution has shown that Trudeau’s concepts of the Canadian people and of one nation, in their final form, no longer allow the development of a distinct, stable, autonomous Quebec culture. Quebec has provisionally re-established a right distance, at least on the parliamentary level, by electing a strong Bloc Quebecois. What will be the final solution?